Destination image and tourist’s satisfaction: the case study of Melaka / Mohd Azizi Jalaluddin, Mohamad Zaki Shaari and Joel Giak Sigar - Jalaluddin, Mohd Azizi; Shaari, Mohamad Zaki; Sigar, Joel Giak (2015)
Numerous authors have argued that destination image can decay it image over time. They point out that time can change the perspectives of tourists on how they perceive particular destination. It is essential for destination managers to understand the destination image held by both local and foreign tourists to ensure their strategies are successfully enforced. Destination image comprises of two dimensions namely as cognitive and affective. The main objective of this study is to identify factors that influence the formation of overall destination image of Melaka and the relationship between overall destination image and tourist’s satisfaction in Melaka. The research was carried out in Melaka, Malaysia on a sample of 367 tourists. The Partial Least Squares structural equation modelling (PLS-SEM) method was employed to examine the relationship among the variables. The result shows that tourist leisure and recreation, economic factors and social environment, as well as culture, history and art have positive influence on a destination image. The PLS-SEM results also indicate that destination image has a positive effect on tourist’s satisfaction.